Vince Flynn Capture or kill - Bentley, Don (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2024)
Azad Ashani tries to thwart an Iranian plot that could trigger a catastrophic conflict in the Middle East while CIA Director Irene Kennedy races to confirm Osama bin Laden's location.